The Paris deception - Turnbull, Bryn (Mira, 2023)
"Sophie Dix fled Stuttgart with her brother as the Nazi regime gained power in Germany. Now, with her brother gone and her adopted home city of Paris conquered by the Reich, Sophie reluctantly accepts a position restoring damaged art at the Jeu de Paume museum under the supervision of the ERR--a German art commission using the museum as a repository for art they've looted from Jewish families. Fabienne Brandt was a rising star in the Parisian bohemian arts movement until the Nazis put a stop to so-called "degenerate" modern art. Still mourning the loss of her firebrand husband, she's resolved to muddle her way through the occupation in whatever way she can--until her estranged sister-in-law, Sophie, arrives at her door with a stolen painting in hand. Soon the two women embark upon a plan to save Paris's "degenerates," working beneath the noses of Germany's top art connoisseurs to replace the paintings in the Jeu de Paume with skillful forgeries--but how long can Sophie and Fabienne sustain their masterful illusion?"--Page 4 of cover.